COMPARATIVE OVERVIEW OF THE ZIONIST MOVEMENT IN CROATIA AND SERBIA UNTIL THE BEGINNING OF WORLD WAR II - Ljiljana Dobrovšak; Haris Dajč (Istorija 20. Veka)
The Zionist movement in the area of the former Yugoslavia first appeared at the beginning of the 20th century. It emerged first in Croatia, where attorney Hugo Spitzer founded the Zionist Society in his home city of Osijek and started publishing the Zionist magazine, Židovska smotra, and organised several Zionist congresses (in Osijek, Slavonski Brod, and Zemun) in order to connect Jews not only within Austria-Hungary, but also from the neighbouring Kingdom of Serbia. After the end of the First World War, the centre of the Zionist movement moved from Osijek to Zagreb and Belgrade. Although the Zionist movement was better organised in Zagreb, where all major Zionist institutions were situated, by the 1930s it spread more and more to Serbia and Belgrade. Through an analysis of contemporary press and available literature, the authors will discuss the influence of Croatian Zionists on Zionists in Serbia and vice versa, and the spread of Zionist movement in the interwar period.